(untitled) (Research, Society and Development, 2024)
Objective: To report the case of an adult polytraumatized patient in a hospital unit, through the Systematization of Nursing Care, con un enfoque en la lesión cerebral traumática. Method: Descriptive and observational study, clinical case type, carried out in a public hospital in southwestern Bahia. Data collection was carried out through anamnesis, physical examination and data collected from the medical records. NANDA, NIC and NOC were used to determine nursing diagnoses and interventions. Results: Twenty-seven nursing diagnoses related to the NANDA domains were identified. Conclusion: The study highlighted the importance of nursing care in providing care to patients suffering from TBI, highlighting the importance of an individualized assessment, capable of favoring a quick and effective approach, to achieve a good prognosis. The Systematization of Nursing Care enabled precise and assertive intervention, which is essential in cases of severe traumatic brain injury.